An analysis and investigation of warranty rework and costs Case Study of a Swedish Contractor - DAEBES, MUNTADAR; YILMAZ, OGUZHAN (My University, 2017)
The purpose of this thesis work is to identify the warranty work and aftermarket work that the case company faces. In recent years the case company has met an increase in the warranty work. The master thesis has been carried out in a Swedish contractor and is limited with remarks from warranty inspection protocols and data collection for four apartment projects. The study is based on interviews with senior executives in the case company. The results in this study show that the three most common defects that occur during the first two years are as follows: cracks on walls/ceilings, cabinet and boxes and doors. This three building parts account for 55.5% of the total number of remarks, based on the warranty inspection reports. The study presents appropriate improvement work to avoid the emergence of the warranty work and to facilitate the follow-up of the warranty work. The main reasons for warranty remarks are based on several different conditions. The causes can be attributed to moisture-related movements, lack of care and maintenance, assembly errors and lack of product selection. The design phase has the major role when it comes to rework. This in turn led to quality errors to occur. Furthermore, the pressure of time in the construction sector has an impact in the result of quality shortcomings. Construction companies are willing to be done in a shorter time than they really need. This naturally leads to stress at the last stage and leading to shortages at the end of the handover of the residence. A closer relationship between the internal organization and the site manager is needed to solve aftermarket problems in a more efficient way. Most of the experiences learned from previous project are not delivered inside the organization, it rather stands with the specific person. Therefore, it is important for the companies to gather information and experience from previous project and deliver it to the project organization. Companies should have strategies to encourage further training so that individuals get better knowledge of the working methods. In order to prevent defects and mistakes during the production phase, experienced personnel from the production management should be involved in the early design phases.
Keywords: Samhällsbyggnadsteknik; Civil Engineering